Navigating Turbulence: ASEAN’s Leadership Challenges in the Human Rights Violation in Myanmar and South China Sea Dispute - Agussalim, Dafri; Wicaksono, Tunggul (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2024)
The Association of Southeast Asian Nations (ASEAN) is one of the most rapidly growing regional organizations, significantly influencing the geopolitical landscape of Southeast Asia and beyond. Despite these successes, however, ASEAN currently faces serious challenges in maintaining its unity, solidarity, and cohesiveness. A critical issue is the divergence in views, attitudes, and policies of member countries on crucial political and security matters. This study explores the concept of leadership within the structure of regionalization in the Association of Southeast Asian Nations (ASEAN). The concept is shaped by structural capabilities derived from the region's resource production and manpower, with charisma playing a crucial role in leadership. Based on this concept, this study explores the leadership role in ASEAN's efforts to address current and upcoming issues, particularly about human rights abuses in Myanmar and South China Sea disputes. This study compares Indonesia's leadership within ASEAN to that of other member states using a qualitative comparative case study design. This method investigates how different elements affect the phenomenon that is being studied. A more nuanced understanding of the complex relationships between various variables, including leadership, domestic turmoil, and regional dynamics, can be obtained through the analysis of cases in real-life contexts. The study posits that ASEAN will not be able to uphold its integrity and accelerate the realization of a harmonious ASEAN society in the future without robust leadership. Unlike in its early years, ASEAN today lacks a leader capable of mobilizing political resources to address and resolve collective issues within the organization.